Μια περιβαλλοντική, τεχνική και οικονομική προσέγγιση για την ηλεκτροδότηση ελλιμενισμένων πλοίων στο λιμάνι του Πειραιά - Καμπύλης, Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2016)
Air pollution is a significant problem for all busy ports around the world and Piraeus port is no exception. Strict regulations about marine fuel’s quality and ship’s emissions have been introduced in several areas of the world obliging ship-owners to take measures in order to make ships more ecological and human friendly. This particular study will focus on the implementation of Cold-Ironing in Piraeus port, as a method for the control and reduction of air pollution caused by ferries, cruise ships and container carriers. Chapter one and two of this study will attempt to present the actual situation in maritime industry, the environmental damage which results from ship’s activity, the negative impact of marine engine’s emissions to human health as well as the basic principals of Cold-Ironing with examples of implementation in other countries. For each type of vessel, it is necessary to create a “Berthing Power Demand Profile” which includes berthing time, average and peak hoteling load and electrical system details such as frequency and primary voltage. Dimensioning of the Cold-Ironing equipment and preliminary design of the shore-side installations, are based on these power demand profiles. The last chapter of this study will focus on the economic aspect of Cold-Ironing both from the perspective of ship-owners and the perspective of port operators.